Small RNA-Sequencing for Analysis of Circulating miRNAs: Benchmark Study - Androvic, Peter; Benesova, Sarka; Rohlova, Eva; Kubista, Mikael; Valihrach, Lukas (The Journal of molecular diagnostics, 2022)
Small RNA-sequencing (RNA-Seq) is being increasingly used for profiling of circulating microRNAs (miRNAs), a new group of promising biomarkers. Unfortunately, small RNA-Seq protocols are prone to biases limiting quantification accuracy, which motivated development of several novel methods. Here, we present comparison of all small RNA-Seq library preparation approaches that are commercially available for quantification of miRNAs in biofluids. Using synthetic and human plasma samples, we compared performance of traditional two-adaptor ligation protocols (Lexogen, Norgen), as well as methods using randomized adaptors (NEXTflex), polyadenylation (SMARTer), circularization (RealSeq), capture probes (EdgeSeq), or unique molecular identifiers (QIAseq). There was no single protocol outperforming others across all metrics. Limited overlap of measured miRNA profiles was documented between methods largely owing to protocol-specific biases. Methods designed to minimize bias largely differ in their performance, and contributing factors were identified. Usage of unique molecular identifiers has rather negligible effect and, if designed incorrectly, can even introduce spurious results. Together, these results identify strengths and weaknesses of all current methods and provide guidelines for applications of small RNA-Seq in biomarker research.
Keywords: mikro RNA; vysoce účinné nukleotidové sekvenování; Sequence Analysis, RNA; Circulating MicroRNA; benchmarking; Humans; sekvenční analýza RNA; cirkulující mikroRNA; High-Throughput Nucleotide Sequencing; MicroRNAs; lidé; Benchmarking